Regression of intracranial meningioma following treatment with nivolumab: Case report and review of the literature. (March 2017) - Gelerstein, Efrat; Berger, Assaf; Jonas-Kimchi, Tali; Strauss, Ido; Kanner, Andrew A.; Blumenthal, Deborah T.; Gottfried, Maya; Margalit, Nevo; Ram, Zvi; Shahar, Tal
Highlight: PD-1 inhibitor immunotherapy may have impact for treatment of refractory meningioma. Abstract: The treatment of refractory meningiomas remains a challenge for both neurosurgeons and neuro-oncologists. There have been no clinical reports of the use or effects of anti-PD-1 therapy in patients with meningioma. We describe a patient whose intracranial meningioma decreased significantly in size after treatment with nivolumab, a monoclonal antibody targeting PD-1, for a concomitant advanced lung cancer. This is the first clinical report suggesting that antibodies targeting PD-1 are effective in treating meningioma. It should encourage further research into the use of checkpoint inhibitors in meningioma.